THU0197 Tofacitinib, an oral janus kinase inhibitor, in the treatment of rheumatoid arthritis: safety and efficacy in open-label, long-term extension studies over 8 years. (15th June 2017) - Wollenhaupt, J; Silverfield, J; Lee, EB; Terry, K; Kwok, K; Abramsky, S; Wang, M; Nduaka, C; DeMasi, R; Wang, L
Abstract : Background: Tofacitinib is an oral Janus kinase inhibitor for the treatment of rheumatoid arthritis (RA). Objectives: The objective of this analysis was to report tofacitinib safety, tolerability and clinical efficacy in long-term extension (LTE) studies with up to 105 months of observation. Methods: Data were pooled from two open-label studies (NCT00413699 [ongoing; database not locked at January 2016 data-cut] and NCT00661661 ) of patients with RA who had participated in Phase 1/2/3 tofacitinib studies. Patients received tofacitinib 5 or 10 mg twice daily (BID) as monotherapy or with background disease-modifying antirheumatic drugs (DMARDs). Primary endpoints were adverse events (AEs) and confirmed laboratory safety data. Secondary endpoints included clinical efficacy measures (American College of Rheumatology [ACR] 20/50/70 response rates, Disease Activity Score using 28 joint counts and erythrocyte sedimentation rate [DAS28-4(ESR)], Health Assessment Questionnaire-Disability Index [HAQ-DI] and clinical disease activity index [CDAI]). Safety data were included up to Month 105 and efficacy data up to Month 90 (n≤100 at Month 96). Results: A total of 4967 patients were treated (mean [max] duration: 1215 [3182] days). Total tofacitinib exposure was 16, 711 patient-years; 77.4% of patients maintained their initial dose. In total, 2370 patients (47.7%) discontinued (AEs: 1131 [22.8%]; insufficient clinical response: 175 [3.5%]). The most common AE classes were infections and infestations (68.9%) and musculoskeletal/connective tissue disorders (39.0%). The most common AEs were nasopharyngitis (18.7%), upper respiratory tract infection (17.2%), bronchitis and urinary tract infection (12.2% each). Serious AEs occurred in 28.6% of patients and serious infection events (SIEs) in 8.8% of patients. Malignancies, excluding non-melanoma skin cancer, were reported in 3.0% of patients. Incidence rates (IR; patients with events per 100 patient-years) for AEs of interest (with 95% confidence intervals [CIs]) and laboratory observations are provided in Table 1. IRs for SIEs and malignancies through Month 105 did not increase compared with reported data through Month 96.1 No new safety risks were identified. Clinical responses were sustained from Month 1 to Month 90 (Table 2). Conclusions: In patients with RA who remained in the LTE studies, tofacitinib (5 or 10 mg BID) with or without background DMARDs was associated with consistent safety through Month 105 and sustained clinical efficacy through Month 90. References: Wollenhaupt J et al. Arthritis Rheumatol 2015; 67 (suppl 10): Abstract 1645. Acknowledgements: Previously presented at ACR 2016 and reproduced with permission. This study was sponsored by Pfizer Inc. Editorial support was provided by M Bell of CMC and was funded by Pfizer Inc. Disclosure of Interest: J. Wollenhaupt Consultant for: Pfizer Inc, Speakers bureau: Pfizer Inc, J. Silverfield Grant/research support from: Pfizer Inc, Speakers bureau: Pfizer Inc, E. B. Lee Consultant for: Pfizer Inc, K. Terry Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, K. Kwok Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, S. Abramsky Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, M. Wang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, C. Nduaka Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, R. DeMasi Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, L. Wang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc